De gamle stier Historien om Menigheten Samfundet, Det Almindelige Samfund og andre sterkttroende - Iversen, Jonas Yassin (Kyrkjefag Profil, 2021)
"This book takes the reader on a historical and theological journey through intense awakenings, decisive church foundations and dramatic schisms in southwestern Norway from the 1820s to the present. Based on extensive source material, the book provides new perspectives on the history of the so-called 'firm believers' and a nuanced presentation of their theological development from a vigorous revival during the first half of the 19th century to today's closed religious communities. The Old Paths: The History of 'Menigheten Samfundet', 'Det Almindelige Samfund' and other 'firm believers' describes a diverse religious tradition marked by deep devotion and intellectual rigour, while also giving the reader a glimpse of prominent church leaders, charismatic preachers and devoted believers. Many in Rogaland and Agder today are familiar with 'lomelendingane' - adherents of the Menigheten Samfundet sect, named after its founder, Bernt Lomeland - in Kristiansand and Egersund, and such similarly named groups of followers as the 'perane' and 'larsane', also in Egersund. All of these groups have traditionally been referred to as 'the firm' or 'the firm believers'. Most works on Norwegian church history include brief descriptions of 'the firm believers', but no scholarly work entirely devoted to their origins and history has previously been published. As such, this book represents the most comprehensive and updated work on 'the firm believers' published to date and it therefore constitutes an important contribution to Norwegian church history. This book will be of value to scholars, students and others with an interest in Norwegian church history, sociology of religion, and closed religious communities. Kyrkjefag Profil is a series established by the Department of Religious Studies at Volda University College. This book is number 41 in the series."